Analisis Persepsi Pengguna Aplikasi Tring Menggunakan Technology Acceptance Model (Tam) - Davin Putra Febriansyah; Aries Dwi Indriyanti (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The rapid development of digital technology has encouraged the public to utilize digital gold investment services, one of which is the Tring Pegadaian application. Although the application offers various features that facilitate investment activities, user acceptance needs to be evaluated to identify the factors influencing its use. This study aims to analyze user acceptance of the Tring Pegadaian application using the Technology Acceptance Model (TAM). A quantitative approach was employed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4 software. Data were collected through questionnaires distributed to 146 users of the Tring Pegadaian application. The results indicate that Perceived Ease of Use has a positive and significant effect on Perceived Usefulness, Perceived Usefulness positively and significantly affects Behavioral Intention to Use, Perceived Ease of Use also positively and significantly affects Behavioral Intention to Use, and Behavioral Intention to Use positively and significantly affects Actual System Use. These findings indicate that perceived ease of use and perceived usefulness play important roles in increasing users' intention, which subsequently encourages the actual use of the Tring Pegadaian application.